2021
DOI: 10.1212/nxi.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ocrelizumab in Blood Leukocytes of Patients With Primary Progressive MS

Abstract: ObjectiveTo analyze the changes induced by ocrelizumab in blood immune cells of patients with primary progressive MS (PPMS).MethodsIn this multicenter prospective study including 53 patients with PPMS who initiated ocrelizumab treatment, we determined effector, memory, and regulatory cells by flow cytometry at baseline and after 6 months of therapy. Wilcoxon matched paired tests were used to assess differences between baseline and 6 months' results. p Values were corrected using the Bonferroni test.ResultsOcre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 29 publications
10
75
4
Order By: Relevance
“…When exploring the ability of these cells to predict secondary autoimmunity at baseline, we found that this was not the case in patients treated previously with natalizumab, who mostly presented a lower percentage of plasmablasts. This agrees with previous data showing that natalizumab and no other disease modifying drugs diminish the percentages of plasmablasts in blood (14,15,24).…”
Section: Discussionsupporting
confidence: 93%
“…When exploring the ability of these cells to predict secondary autoimmunity at baseline, we found that this was not the case in patients treated previously with natalizumab, who mostly presented a lower percentage of plasmablasts. This agrees with previous data showing that natalizumab and no other disease modifying drugs diminish the percentages of plasmablasts in blood (14,15,24).…”
Section: Discussionsupporting
confidence: 93%
“…We suggest that this failure is related to depletion of naive and memory B lymphocytes that occurs under ocrelizumab treatement. 22 These cells are responsible for the generation of antibody production, and therefore their depletion harms humoral protection.…”
Section: Discussionmentioning
confidence: 99%
“…CD20 + T cells have been found to be increased in MS patients [26], representing almost 20% of all CD20 + expressing cells [27]. It has been recently showed that ocrelizumab reduces CD20 + T cells after 6 months of treatment [28], in line with similar findings found during treatment with rituximab [29]. We showed that patients with persistent early inflammatory activity during the first year of treatment had higher levels of CD8 + cells at 6-month FU as compared with stable patients.…”
Section: Discussionmentioning
confidence: 99%